THE ROLE OF THE E-PROCUREMENT IN THE PURCHASING PROCESS - Pop Sitar Corina (Annals of the University of Oradea: Economic Science, 2011)
This article aims to examine the role of the E-procurement forms in the six phases of the purchasing process. The paper starts with an introductory part about the purchasing process. Next, based on a literature review we selected and defined the most important forms of E-procurement. Furthermore, we develop a theoretical framework that suggests what form of E-procurement is best to use in every phase of the purchasing process. At the end of the paper we draw conclusions and we set some ground rules for managers regarding to the implementation of an E-procurement form.